Adenosine Deaminase in Diagnosis of Tuberculosis: A Review (Anwer Khan Modern Medical College Journal, 2014)
The diagnosis of tuberculosis (TB) continues to be a challenge in clinical practice. Traditional diagnostic methods are very useful but do not provide enough sensitivity and specificity. Adenosine deaminase (ADA) has been developed and widely used for the diagnosis of TB. ADA is an enzyme that increases in TB because of the stimulation of T-cell lymphocytes by mycobacterial antigens. This article reviews the characteristics, metabolism and clinical uses of ADA for the diagnosis of TB in clinical practices. There is sufficient data supporting yield of ADA in various body fluids for the diagnosis of TB. ADA may be used for early diagnosis of TB, especially in case of negative acid fast bacilli (AFB) smear from the body specimens. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21132 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 43-48